Estimation of guitar sound quality - BOEHM, Tomira; MIKLASZEWSKI, Kacper; BLUTNER, Friedrich; MEINEL, Eberhard (Archives of Acoustics, 1986)
The described investigation was aimed at the determination of the subjective and objective quality of sound of four classic guitars. The investigation of the subjective sound quality — carried out in the Laboratory of Music Acoustics, Academy of Music in Warsaw — consisted of two parts: general and parametric. The following parameters was used: brightness, timbre dispersion over the instrument scale, fullness, carrying power, clearness, dynamics. The listeners were students and co-workers in this laboratory. Investigations of the objective quality carried out in Zwota (GDR) resulted in sound pressure level histograms — presented in 20 diagrams for 20 frequency bands covering the full range of sound frequencies produced by the investigated instruments. The analysis of these histograms shows a significant correlation with the results of the subjective quality estimation.